2018
DOI: 10.3390/medicina54020011
|View full text |Cite
|
Sign up to set email alerts
|

An Effect of Culture Media on Epithelial Differentiation Markers in Breast Cancer Cell Lines MCF7, MDA-MB-436 and SkBr3

Abstract: Background and objectives: Cell culture is one of the mainstays in the research of breast cancer biology, although the extent to which this approach allows to preserve the original characteristics of originating tumor and implications of cell culture findings to real life situations have been widely debated in the literature. The aim of this study was to determine the role of three cell culture media on transcriptional expression of breast cancer markers in three breast cancer reference cell lines (MCF7, SkBr3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Culture and seeding conditions of MCF-7 biological replicate cultures (sub-clones A1 and A2) Samples were collected from MCF-7 cell line (ATCC, HTB-22) that has been used in our laboratory for previous studies [56]. Samples from different passages were cryopreserved during culturing at different time points.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Culture and seeding conditions of MCF-7 biological replicate cultures (sub-clones A1 and A2) Samples were collected from MCF-7 cell line (ATCC, HTB-22) that has been used in our laboratory for previous studies [56]. Samples from different passages were cryopreserved during culturing at different time points.…”
Section: Methodsmentioning
confidence: 99%
“…The MCF-7 samples from previous study in our laboratory [56] were used to validate the reference gene triplet in cells undergoing different nutrient conditions, i.e. cultured in different media.…”
Section: Culturing Conditions Of Mcf-7 Cultures In Nutrient Stressmentioning
confidence: 99%
“…Keratinocyte differentiation, skin development and epidermis development gene sets enriched in the high PPS20 group include many genes belonging to the keratin family, among which KRT16 has been used as a basal cell marker [28,29]; KRT17 has been shown to induce cancer stem cell-like properties in cervical cancer [30] and tumor growth, motility and invasion in gastric cancer [31], which is also associated with poor prognosis in breast cancer [32]. Formation of primary germ layer and endoderm gene sets were also enriched in tumors with high PPS20.…”
Section: Molecular Characteristics Of Pps20-identified Pdac Sub-groupsmentioning
confidence: 99%
“…Several studies have shown that the composition of basal medias has a significant impact on the results of their experiments (Ariffin et al, 2016;Kim et al, 2015;Pirsko et al, 2018;Selenius et al, 2019;Tomoya Kawakami, 2016). However, culture media and supplementation remain a largely overlooked experimental parameter.…”
Section: Introductionmentioning
confidence: 99%